Supporting strategies to improve air quality over harbour areas - Sorte, Sandra Sofia Silva (2022)
Despite their key contribution to economic development, harbours pose environmental threat, affecting air quality, local climate, and human health, due to the release of several pollutants. Poor local air quality episodes are particularly concerning when harbours are located near densely populated urban areas, threatening inhabitants’ health. This Thesis was focused on the assessment of the impact of harbour emissions on the air quality over harbours and their surrounding urban areas, with a final goal of producing guidelines to support decision-making in the harbour sector and air quality management, using Port of Leixões as a case-study. After reviewing the state-of-the-art in this research field, a high-resolution emission inventory was developed, based on the two most used methodologies within the scientific community. Data about ship and cargo handling equipment were compiled, allowing the quantification of emissions and identification of their main sources. The comparison of the two methodologies indicates that a new harmonized methodology is recommended, besides the need of continuous update of emission factors and activity data. Having the detailed emission inventory, the community-scale webtool C-PORT was applied for the first time in European harbours to simulate the impact of the maritime emissions on local air quality. The comparison of modelled and observed values validated its application for the case study of Port of Leixões. The highest PM10 concentrations were found near the South Container Terminal of Port of Leixões, while NOx concentrations above 100 µg/m3 were also found near the highway. Land-based emission sources exhibited the highest contribution (around 80 %) to the PM10 concentrations in the study area, while 50 % of NOx concentration was due to docked ships. Mitigation measures were investigated and assessed to improve air quality in harbours and their surroundings. In a case-study, pollutant dispersion was addressed, aiming to control fugitive petcoke emissions and their impact on Port of Aveiro’s neighbour communities. Optimal structure, size and position of a physical barrier were defined based on numerical and physical modelling, achieving a maximum reduction in petcoke dust reaching the nearby residential area of 74 – 88 % for the most frequent/critical wind directions. The studied barrier has been implemented in the field and monitoring campaigns are currently being carried out to assess its effectiveness.